Pricing Item Attributes And Online Ratings Determine Apparel Platform Buying Intentions: Harga Atribut Barang Dan Penilaian Daring Menentukan Niat Beli Platform Pakaian - Lusi Rahmawati Rahmawati; Amirah Najchan Hibah; Agustina Santi; Siti Anisatul Masulah; Sigit Hermawan (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid expansion of digital transformation has fundamentally reshaped the global retail landscape, particularly within the digital apparel sector. Specific Background Amidst fierce market competition, digital platforms like Shopee strive to capture young consumer demographics by optimizing various transaction elements. Knowledge Gap Although factors driving online transactions are widely recognized, empirical studies show inconsistencies regarding how financial costs, physical merchandise standards, and electronic word-of-mouth interact simultaneously through post-transaction fulfillment to stimulate commercial choices. Aims This study investigates how pricing, item attributes, and online ratings determine buying intentions, specifically examining the mediating role of customer fulfillment within the digital apparel industry. Results Quantitative path analysis of university students reveals that pricing, item attributes, and online ratings directly and significantly stimulate buying intentions. Furthermore, physical merchandise standards uniquely dictate direct customer fulfillment, whereas customer satisfaction serves as a crucial mediating variable connecting these antecedent factors to final purchasing choices. Novelty This research demonstrates the distinct pathways of commercial decision-making, highlighting that while financial costs and peer evaluations drive immediate interest, sustained post-transaction fulfillment relies strictly on tangible physical standards. Implications Digital retail managers must implement competitive pricing frameworks and encourage authentic peer evaluations while prioritizing physical manufacturing standards to maximize consumer fulfillment and long-term commercial acquisition. Highlights: Competitive costs and electronic word-of-mouth directly stimulate consumer purchasing choices. Physical merchandise characteristics establish strong post-transaction fulfillment among young demographic shoppers. Client gratification successfully mediates the pathway toward final commercial transactions. Keywords: Customer Satisfaction, Apparel Platform, Pricing Strategy, Buying Intentions, Online Ratings